Students' perceptions and experiences towards the educational value of online videos - Hajhashemi, Karim; Caltabiano, Nerina; Anderson, Neil (Australian Educational Computing, 2016)
In conjunction with the arrival of emerging technologies, many universities are encouraging their educators to rethink and reframe their teaching approaches and delivery methods. Integrating different types of media to enhance delivery of subject materials to higher education students is growing in national and international importance. As a response to the technology-enhanced approach, a more student-centred experience that actively engages students is promoted. This paper focuses on student perceptions of the value of online videos in relation to their learning and reports on interviews conducted with students in a rural and remote university in Australia. It provides a clear voice on their views concerning the benefits, and challenges of online video use, along with any positive or negative suggestions regarding their experience of the technology. [Author abstract]